Entertainment Computing - ICEC 2015 14th International Conference, ICEC 2015, Trondheim, Norway, September 29 - Ocotober 2, 2015, Proceedings - Chorianopoulos, Konstantinos; Divitini, Monica; Baalsrud Hauge, Jannicke; Jaccheri, Letizia; Malaka, Rainer (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2015)
This book constitutes the refereed proceedings of the 14th International Conference on Entertainment Computing, ICEC 2015, held in Trondheim, Norway, in September/October 2015. The 26 full papers, 6 short papers, 16 posters, 6 demos and 6 workshops/tutorial descriptions presented were carefully reviewed and selected from 106 submissions. The multidisciplinary nature of Entertainment Computing is reflected by the papers. They focus on computer games; serious games for learning; interactive games; design and evaluation methods for Entertainment Computing; digital storytelling; games for health and well-being; digital art and installations; artificial intelligence and machine learning for entertainment; interactive television and entertainment.